Factores socioculturales y satisfacción del adulto sobre el cuidado de enfermería Hospital Belen de Trujillo - Mariños Vanini, Marisol Araceli (2013)
The present investigation study of a descriptive-correlational and transversal section sort was done by the intention of determinate the existing relation between the sociocultural factors, and the level of satisfaction with the care of Infirmary in hospitaliz adult. Belen Hospital of Trujillo. The sample was constituted by 160 adults of medicine to those who applied them the previous instruments proofs of confiabilidad through the Alfa of Crombach (0.8157 ), and validez of trial of experts. the information was processed using the Statistical Package for the Social Sciences (SPSS) to every variable, the independence of criteria test (X2) was used in the statistical analysis coming to the following conclusions: The majority of the hospitalized adults are moderately satisfied with a rate of 45 %, followed by those who recounted satisfaction with a rate of 28.7 % and 26.2% who showed dissatisfaction. Regarding the sociocultural factors variable, it was determined that 50 % was elder, 50 % of the adults were male, 65 % had a low grade of instruction and likewise 50 % came from the region of the highlands. When relating the socio cultural factors to the grade of satisfaction, it was found that sex does not keep relation with it; whereas the age, the grade of instruction and the origin, keep a statistically significant relation.